2012
DOI: 10.1002/msj.21324
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Psychiatric Services in Primary‐Care Setting

Abstract: Psychiatric disorders, particularly depression and anxiety disorders, are common in primary-care settings, though often overlooked or untreated. Depression and anxiety disorders are associated with a poorer course for and complications from common chronic diseases such as diabetes mellitus and coronary heart disease. Integrating psychiatric services into primary-care settings can improve recognition and treatment of psychiatric disorders for large populations of patients. Numerous research studies demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
13
0
2
Order By: Relevance
“…Our results are similar to prior studies that PCPs are particularly likely to refer patients to mental health specialists when symptoms are severe (Steele et al 2010), and primary-care pediatricians practicing in clinics with onsite psychiatrists or other mental health specialists were more likely to request psychiatric consultation compared with those without on-site psychiatric services (Cerimele et al 2012). However, the primary care providers in co-located settings seemed to have moderate levels of comfort relative to managing/treating psychiatric illnesses.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are similar to prior studies that PCPs are particularly likely to refer patients to mental health specialists when symptoms are severe (Steele et al 2010), and primary-care pediatricians practicing in clinics with onsite psychiatrists or other mental health specialists were more likely to request psychiatric consultation compared with those without on-site psychiatric services (Cerimele et al 2012). However, the primary care providers in co-located settings seemed to have moderate levels of comfort relative to managing/treating psychiatric illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…It was not surprising that the interval between PCP referral and visit to the co-located mental health specialist was relatively shorter than referrals to an external mental health provider. This further reinforces the benefits of the co-located integrated care model where the psychiatrist/mental health specialist is on site at the primary-care clinic and often available for same say consultation (Cerimele et al 2012). …”
Section: Discussionmentioning
confidence: 53%
“…Although promoted as a mechanism to improve the care of children with MH issues, little is known about physically locating a MH professional near or in a pediatric practice or about the influence of on-site MH professionals on pediatricians’ activities with regard to child/adolescent MH issues. 14–17 In an early examination of referrals for child/adolescent MH problems by pediatricians, Williams et al, 2005, found that pediatricians reported that they were likely to use a MH specialist who was on-site in their practice but would be less likely to use either psychopharmacology or behavioral health consultation by phone. 18 Guevara and colleagues (2009) examined pediatricians identified from the American Medical Association’s 2004 physician directory and found that 17% had an onsite MH professional and that those with an onsite MH professional were more likely to consult with and refer to that professional.…”
Section: Introductionmentioning
confidence: 99%
“…A testimonial on the company website 13 from a psychiatrist states that the test might be used by family practice physicians who are not as well-trained as psychiatrists to diagnose MDD. While the basis for this statement is not clear (family practice residencies do include training in diagnosing MDD), there are better, less costly models for diagnosing MDD in the general practice setting, such as integrated collaborative care.…”
mentioning
confidence: 99%
“…While the basis for this statement is not clear (family practice residencies do include training in diagnosing MDD), there are better, less costly models for diagnosing MDD in the general practice setting, such as integrated collaborative care. 13 Back in the 1980s, the argument was made by Carroll and others that MDD was too heterogeneous a category to be useful for the study of biomarkers.…”
mentioning
confidence: 99%